Effect of Magnetic Field Configuration of Dual Magnetron on Carbon Based Films Properties; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Yuriev Yu. N. Yuri Nikolaevich; Zaitsev D. A. Danila Aleksandrovich; Sidelev D. V. Dmitry Vladimirovich; Tupikova O. S. Olga Sergeevna (Technologies of Electrophysical Methods of Materials Treatment, 2014)
Title screen